THE EFFECT OF INVESTMENT ON ECONOMIC GROWTH IN EAST KALIMANTAN DURING THE COVID-19 IMPACT (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Economic growth is a measure of the economic progress of a country or region and one of the drivers of economic growth is investment. The purpose of this study is to analyze the effect of investment on economic growth in East Kalimantan Province during the Covid-19 impact, starting from 2019-2021. The method used in this study is multiple linear regression. The results showed that the FDI variable had a significant effect on economic growth while PMDN had no effect on economic growth in East Kalimantan. This research is expected to provide useful information for making policies to increase economic growth in East Kalimantan Province through investment.
Keywords: Economic Growth; Investment; PMA; PMDN